Polymorphism in the IL-1 beta promoter is associated with IgG antibody response to circumsporozoite protein repeats of Plasmodium vivax - Capobianco, Marcela Petrolini [UNESP]; Cassiano, Gustavo Capatti; Storti-Melo, Luciane Moreno; Pimenta, Tamirys Simao; Drummond Rodrigues, Ana Paula; Gomes Arruda, Jose Eduardo; Pinto, Marcia Ribeiro; Souza Baptista, Andrea Regina de; Pratt-Riccio, Lilian Rose; Bonini-Domingos, Claudia Regina [UNESP]; De Oliveira-Ferreira, Joseli; Dantas Machado, Ricardo Luiz [UNESP] (Oxford Univ Press, 2020)
Background: It is well established that infection by Plasmodium vivax is a result of host-parasite interactions. In the present study, association with the IL1/IL2 cytokine profiles, anticircumsporozoite protein antibody levels and parasitic loads was evaluated in individuals naturally infected with P. vivax in an endemic area of the Brazilian Amazon. Methods: Molecular diagnosis of P. vivax and variants was performed using the PCR-RFLP method and IL1B -511C>T, IL2 -330T>G and IL2+114T>G polymorphisms were identified using PCR-RFLP and allele-specific PCR. IL-1 beta and IL-2 cytokine levels were detected by flow cytometry and circumsporozoite protein (CSP) antibodies were measured by ELISA. Results: Three variants of P. vivax CSP were identified and VK247 was found to be the most frequent. However, the prevalence and magnitude of IgG antibodies were higher for the VK210 variant. Furthermore, the antibody response to the CSP variants was not associated with the presence of the variant in the infection. Significant differences were observed between the single nucleotide polymorphism (SNP) -511T>C in the IL1B gene and levels of antibodies to the VK247 and P. vivax-like variants, but there were no associations between SNPs in IL1 and IL2 genes and their plasma products. Conclusions: Individuals with the rs16944 CC genotype in the IL1 beta gene have higher antibody levels to the CSP of P. vivax of VK247 and P. vivax-like variants.
Keywords: antibodies; circumsporozoite protein; IL-1; IL-2; Plasmodium vivax; polymorphisms